ANALISIS PERSEPSI GURU TERHADAP PELATIHAN MEDIA INTERAKTIF GOOGLE SITES DI SMPN 4 MANGARABOMBANG - Rusmita; Ghaisani Aulia; Kasman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the implementation of Google Sites as an interactive and collaborative learning medium in the digital era. The research explores how the platform is utilized to present learning materials, facilitate interaction, and support student collaboration. The objective is to describe the effectiveness of Google Sites in enhancing learning engagement and to assess its function as an accessible instructional management tool. The method used was a qualitative descriptive approach through observation, content analysis of learning pages, and interviews. The results of the study indicate that Google Sites is able to provide an organized material structure, responsive collaborative features, and multimedia integration that enhances conceptual understanding. Students reported a more independent and directed learning experience, while teachers found it easier to organize, update, and monitor learning activities. This study contributes by mapping the detailed use of Google Sites in the context of digital learning and providing technical recommendations for optimizing this platform at other educational levels and for further research.